T cell kinetics reveal expansion of distinct lung T cell subsets in acute versus in resolved influenza virus infection - Eriksson, Malin; Nylén, Susanne; Grönvik, Kjell-Olov (Frontiers in Immunology, 2022)
Influenza virus infection is restricted to airway-associated tissues and elicits both cellular and humoral responses ultimately resulting in generation of memory cells able to initiate a rapid immune response against re-infections. Resident memory T cells confer protection at the site of infection where lung-resident memory T cells are important for protecting the host against homologous and heterologous influenza virus infections. Mapping kinetics of local and systemic T cell memory formation is needed to better understand the role different T cells have in viral control and protection. After infecting BALB/c mice with influenza virus strain A/Puerto Rico/8/1934 H1N1 the main proportion of activated T cells and B cells expressing the early activation marker CD69 was detected in lungs and lung-draining mediastinal lymph nodes. Increased frequencies of activated cells were also observed in the peripheral lymphoid organs spleen, inguinal lymph nodes and mesenteric lymph nodes. Likewise, antigen-specific T cells were most abundant in lungs and mediastinal lymph nodes but present in all organs studied. CD8+CD103-CD49a+ lung-resident T cells expanded simultaneously with timing of viral clearance whereas CD8+CD103+CD49a+ lung-resident T cells was the most abundant subset after resolution of infection and antigen-specific, lung-resident T cells were detected up to seven months after infection. In conclusion, the results in this detailed kinetic study demonstrate that influenza virus infection elicits adaptive immune responses mainly in respiratory tract-associated tissues and that distinct subsets of lung-resident T cells expand at different time points during infection. These findings contribute to the understanding of the adaptive immune response locally and systemically following influenza virus infection and call for further studies on the roles of the lung-resident T cell subsets.